Structural Modelling of Homebuyer Behavior in The Residential Housing Market - K.M, Kavya; Almeida, Shaeril Michael (International Journal of Accounting and Economics Studies, 2025)
Rapid urbanization has significantly increased the demand for residential housing, underscoring the need for real estate retailers to comprehend the factors that drive homebuyers' purchasing behavior. This study employs a Structural Equation Modelling (SEM) framework to examine the critical determinants of purchase intention within the residential real estate sector. Key constructs analyzed include housing attributes, financial and economic considerations, location and service quality, environmental concerns, brand image, and information sources. The SEM analysis elucidates the strength and significance of the relationships among these variables, providing a comprehensive understanding of consumer decision-making processes. The findings yield actionable insights for real estate practitioners, offering guidance for the development of targeted marketing strategies, enhanced customer engagement practices, and improved service delivery. By aligning their offerings with buyer expectations, real estate firms can foster stronger client relationships and enhance their competitive positioning in a dynamic housing market.
Keywords: Purchase Intention, Consumer behavior, Homebuyers, Real Estate